KAJIAN OPERASI PASAR KOMODITAS BAWANG PUTIH DI PROVINSI JAMBI - Nida Kemala (Jurnal MeA (Media Agribisnis), 2020)
The research was conducted with the aims as the operation describing of garlic market, garlic price and determining the duration of time required  to restore its normal price. The type of data was secondaries data with applying a deststudy  collection method. Data were analyzed descriptively equipped with a single sample Chi-Square non-parametric statistical test. The results of the study showed that The operation of the Garlic engaged several department e.g. Jambi Province Industry and Trade Service (Disperindag), Ministry of Trade of  the Republic of Indonesia, Jambi Province Food Security Service, and Indonesian onion and tuber vegetable business association (Bahrindo). A total of 3.2 tons of imported garlic were distributed to the wholesale level at a price of Rp. 22,000 per kg, so that the price at the consumer level was Rp. 32,000 per Kg. The lowest average daily price was Rp.18,000 per Kg (in January) and the highest average price was Rp.46,419 per Kg (in May). In the period  January to May, the average price increase reached 157.8%, while the decline in May-December was smaller than the previous increase of only 65.9% (Average price in December was Rp.25,800 per Kg). The price of garlic after market operations continued to show an increase not only due to the presence of Ramadan and Idul Fitri, but also the supply of garlic imports was too slow. The highest price fluctuation occurred in May where the price range was Rp.70,000 per kg (Rp. 30,000 to Rp.100,000 per kg). The time required to return the price of garlic in the field to the normal price set by the government was 50 days or nearly two months from the started periode of market operations.